An optimized comet-based in vitro DNA repair assay to assess base and nucleotide excision repair activity - Vodenkova, Sona; Azqueta, Amaya; Collins, Andrew; Dusinska, Maria; Gaivão, Isabel; Møller, Peter; Opattova, Alena; Vodicka, Pavel; Godschalk, Roger W L; Langie, Sabine A S (Nature protocols, 2020)
This optimized protocol (including links to instruction videos) describes a comet-based in vitro DNA repair assay that is relatively simple, versatile, and inexpensive, enabling the detection of base and nucleotide excision repair activity. Protein extracts from samples are incubated with agarose-embedded substrate nucleoids ('naked' supercoiled DNA) containing specifically induced DNA lesions (e.g., resulting from oxidation, UVC radiation or benzo[a]pyrene-diol epoxide treatment). DNA incisions produced during the incubation reaction are quantified as strand breaks after electrophoresis, reflecting the extract's incision activity. The method has been applied in cell culture model systems, human biomonitoring and clinical investigations, and animal studies, using isolated blood cells and various solid tissues. Once extracts and substrates are prepared, the assay can be completed within 2 d.
Keywords: Cell Line; kometový test; buněčné linie; zvířata; Humans; DNA Repair; oprava DNA; Comet Assay; lidé; Animals